Otoritas Keislaman di Indonesia: Sebuah Pembacaan Ulang - Mardian Sulistyati (Studia Islamika, 2022)
Ismail Fajrie Alatas. 2021.  What Is Religious Authority? Cultivating Islamic Communities in Indonesia. Princeton & Oxford: Princeton University Press.This book discusses the authority of the source of knowledge of the saints in the archipelago. The stories and cases in this book show how the diversity and uniqueness of the previous saints crossed and merged into the complex culture of the archipelago while opening up new channels for transmitting the teachings of the Prophet. The main argument is the ethnographic and anthropological proof of how hard work of translation, mobilization, collaboration, and political competition are the key elements that shape the strength and diversity of the understanding of Islam in Indonesia. There is a close connection between the prophetic past and every life’s cultural particularity, which transcends regional boundaries. Thus, instead of reinforcing the view that Islam is a “finished religion” and monolithic, this finding shows us that Islam is a “religion that has always become” and pluralistic.